Pembelajaran Akidah Akhlak Inovatif: Jawaban Atas Tantangan Era Digital untuk Penguatan Karakter Keagamaan Siswa MAN 1 Tuban - Nur Khofifatun Nisah; Sholikah Sholikah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the challenges of the digital era and examine innovative Aqidah Akhlak learning strategies in strengthening students’ religious character at MAN 1 Tuban. The digital era presents both opportunities and challenges for Islamic education. While digital technology enables more engaging learning processes, it also poses serious challenges, such as social media addiction, low digital literacy, behavioral changes, and unequal access to technology, which may weaken students’ religious values. This research employs a qualitative approach with a case study design. Data were collected through non-participant observation, semi-structured interviews with teachers, students, school leaders, and parents, as well as relevant documentation. The data were analyzed using thematic analysis, with validity ensured through the triangulation of sources and methods. The findings reveal that the primary challenges in strengthening students’ religious character include the excessive use of social media, a decline in the quality of worship, a limited ability to critically assess religious information, and reduced social interaction. To address these challenges, MAN 1 Tuban implements innovative Aqidah Akhlak learning through interactive digital media, active learning methods, curriculum integration, teacher competency development, and collaboration with parents and the community. These innovations play a significant role in reinforcing students’ religious character, particularly in fostering discipline in worship, religious attitudes, responsibility, and moral integrity amid the rapid flow of digital culture. Keywords: Aqidah Akhlak, Digital Era, Learning Innovation, MAN 1 Tuban, Religious Character